Effects of envelope thermophysical properties on indoor air temperature of a terrace house [electronic resource] - Azliza Azila Kamdzi, 1984- (2008)
Project Paper (Sarjana Muda Kejuruteraan Mekanikal)) - Universiti Teknologi Malaysia, 2008